İlköğretim 4. ve 5. sınıf Din Kültürü ve Ahlak Bilgisi Öğretimi dersi müfredatlarının mukayesesi : (1949-2000) - Acar, Ayşe (My University, 2006)
Milli Eğitim Bakanlığı ilkokullardaki din öğretimi hakkında 1.2.1949 tarihli bir genelgeyle Din derslerinin ilkokulların 4. ve 5. sınıflarında haftada ikişer saat olmak üzere gösterileceği ve bu derslerin Diyanet İşleri Başkanının reisliğinde toplanan özel komisyonca hazırlanmış ve Talim Terbiye Heyetince tatbiki uygun görülmüş olan müfredat rultusunda okutulacağı belirtilmiştir. İhtiyari olarak okutulan ilk din dersleri 1950 yılında program içine alınmış ve 1982 yılına kadar da Din Bilgisi dersi ve Ahlak dersi ayrı ayrı okutulmuştur. Araştırmamızın konusu İlkokulların 4. ve 5. sınıflarında okutulan 1949 yılı ile son müfredat olan 2000 yılı müfredat programının program geliştirme yönünden incelenmesidir.

The date of 1th February of 1949 notice about religion teaching in schools of National Education Ministry, put the lesson Religion Culture to fourth level and fifth level classes of primary school’s lesson’s curriculum by teaching two times a week to students and it has been defined that these lessons will be teached depend on curriculum programme which was prepared by special commission, was got together by Religious Affairs Chief and was appoved of utilization by Instruction and Education Commission. The first religion culture lesson, which has been tesched in the way optional, was put into programme in 1950 and under the name of the lessons of Religion Culture and Ethic Instruction was teached seperately. Our research theme is about appreciation of curriculum programme of the lesson of Religion Culture and Ethic Instruction of the year 1949 and the year of 2000 that is the last the last curriculum programme by comparing the Religion Culture’s curriculum programmea of 1949 and of 2000 and our research theme is also about to analyse the curriculum programme of the year 2000 in terms of improving this curriculum programme. Also ayse_acar_ekler.pdf file is in the CD.This file includes the diagrams.
Keywords: Din Eğitimi; Din Kültürü ve Ahlak Bilgisi Öğretimi Dersi _Müfredat